A determination of areas of biocorrosion development on the route of a main gas pipeline in the Western region of Ukraine - Polutrenko, Myroslava; Kryzhanivs’kyy, Yevstakhiy; Fedorovych, Yaroslav (Geology, Geophysics and Environment, 2020)
A determination of soil corrosivity on three sections of a main gas pipeline in the Western region of Ukraine has been carried out. We have distinguished areas of development of biocorrosive processes with the participation of sulphate-reducing bacteria (SRB). Soil evaluation by the degree of corrosivity has been conducted. We used weight, titrimetric, gravimetric methods, pH-metry, ten-fold limit dilution method and Postgate nutrient medium B for culturing SRB. It has been established that the soil in the first area selected along the lower generatrix of the main gas pipeline has a high degree of corrosivity. It was ascertained that corrosive metal damage increases in the “ferrozone” with the growth of metal exposition time from 24 to 72 hours. The soil selected in the middle part and from above the pipeline refers to soils with a normal degree of corrosive activity. Innovative biostable insulating coatings based on bituminous-polymerous mastic MBPID-1 have been developed, modified with organic inhibitors from the class of quaternary ammonium salts and amines. Regularities of influence of nature of nitrogen-containing corrosion inhibitors of industrial production M, N, L, H and K on the corrosion rate of 17G1S steel for 180 days have been established. It was found that the corrosion rate of steel specimens remained unchanged throughout the study in variants with the presence of inhibitors H and K in the test systems, which indicated their bioresistance to the effect of SRB bacteria.